Influence of Laser Remelting on Creep Resistance in Ti-6Al-4V Alloy with Thermal Barrier Coating - de Freitas, Filipe Estevão (2025)
Ti-6Al-4V alloys with a thermal barrier coating (TBC) have been applied in aeronautical components as turbine blades to provide oxidation resistance and thermal protection, enabling higher operating temperatures and extending component lifespan. Research into TBCs with laser surface modification has investigated improving their mechanical and thermal properties. This study assessed the creep behavior of Ti-6Al-4V alloy with a TBC, where the coating was applied via CO2 laser-remelted plasma spraying. Creep tests were conducted at a constant temperature and a load ranging from 500 to 700 °C at 125 MPa. The microstructure and fractography of the specimens were also investigated. The investigation also included microstructural and fractographic analyses of the specimens. The results indicate that the laser-remelted TBC provided effective thermal protection and increased oxidation resistance, with the stationary creep rate at 600 °C reduced by 50% and the creep rupture life extended by 20%. Observations revealed typical ductile fractures characterized by equiaxed dimples and a homogeneous microstructure with an equiaxed dual-phase (α+β) structure near the fracture zone.